2019
DOI: 10.1038/s41467-019-08895-7
|View full text |Cite
|
Sign up to set email alerts
|

Circulating myocardial microRNAs from infarcted hearts are carried in exosomes and mobilise bone marrow progenitor cells

Abstract: Myocardial microRNAs (myo-miRs) are released into the circulation after acute myocardial infarction (AMI). How they impact remote organs is however largely unknown. Here we show that circulating myo-miRs are carried in exosomes and mediate functional crosstalk between the ischemic heart and the bone marrow (BM). In mice, we find that AMI is accompanied by an increase in circulating levels of myo-miRs, with miR-1, 208, and 499 predominantly in circulating exosomes and miR-133 in the non-exosomal component. Myo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
159
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(162 citation statements)
references
References 39 publications
2
159
0
1
Order By: Relevance
“…Several studies have confirmed the potential of circulating miR-208a and miR-208b, miR-499, miR-133a and miR-1 as sensitive and specific biomarkers of cardiac injury in cardiovascular disease (Fung et al, 2019;Islas and Moreno-Cuevas, 2018;Shi and Yang, 2016). Furthermore, circulating miR-133 and miR-1 participate in the mobilization of progenitor cells and other accessory cells from bone marrow to the peripheral circulation, which is the key procedure in the recovery of cardiac function after cardiac ischemic injury (Cheng et al, 2019).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Several studies have confirmed the potential of circulating miR-208a and miR-208b, miR-499, miR-133a and miR-1 as sensitive and specific biomarkers of cardiac injury in cardiovascular disease (Fung et al, 2019;Islas and Moreno-Cuevas, 2018;Shi and Yang, 2016). Furthermore, circulating miR-133 and miR-1 participate in the mobilization of progenitor cells and other accessory cells from bone marrow to the peripheral circulation, which is the key procedure in the recovery of cardiac function after cardiac ischemic injury (Cheng et al, 2019).…”
Section: Introductionmentioning
confidence: 92%
“…Exosome-miRNAs are selectively and preferentially transferred to bone marrow monocytes where they (miR-1a, not miR-133a, miR-499 or miR-208, directly target the 3' UTR of CXC chemokine receptor 4 (CXCR4)) inhibit the expression of CXCR4 and mediate progenitor cell mobilization. Mobilizing progenitor cells and other accessory cells in bone marrow to peripheral circulation is a key procedure in the recovery of cardiac function after cardiac ischemic injury (Cheng et al, 2019).…”
Section: Myocardial Infarctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes secreted by stem cells act as inhibitors of tumour angiogenesis and modulators of a tumour secretome and growth . Circulating myocardial microRNAs carried by exosomes are responsible for the cross‐talk between ischemic heart and bone marrow and thereby make possible the systemic response to cardiac injury required for cardiac repair and circulating microRNAs were involved in signalling causing pre‐term birth in mice . Since exosomes can carry cargo across the blood‐brain barrier and they lack an immune response, they play an important role in the development and progression of neurodegenerative and mental diseases, as well as in neurophysiological processes .…”
Section: Exosomesmentioning
confidence: 99%
“…In the literature, many clinical studies assessed circulating miRNA levels in peripheral blood for diagnosing, predicting, and monitoring human diseases (158)(159)(160)(161)(162)(163), including cardiac and vascular disease (CVD) (164)(165)(166)(167)(168)(169). For example, the combination of miR-34a-5p and fibrinogen levels have been reported as a useful tool in differentiating pre-thrombotic status in patients with stable coronary artery disease (165).…”
Section: Emerging Challenge Of Bench Studies For Early Detecting Andmentioning
confidence: 99%